Allergenic pollen season variations in the past two decades under changing climate in the United States. (7th November 2014) - Zhang, Yong; Bielory, Leonard; Mi, Zhongyuan; Cai, Ting; Robock, Alan; Georgopoulos, Panos
Abstract Many diseases are linked with climate trends and variations. In particular, climate change is expected to alter the spatiotemporal dynamics of allergenic airborne pollen and potentially increase occurrence of allergic airway disease. Understanding the spatiotemporal patterns of changes in pollen season timing and levels is thus important in assessing climate impacts on aerobiology and allergy caused by allergenic airborne pollen. Here, we describe the spatiotemporal patterns of changes in the seasonal timing and levels of allergenic airborne pollen for multiple taxa in different climate regions at a continental scale. The allergenic pollen seasons of representative trees, weeds and grass during the past decade (2001–2010) across the contiguous United States have been observed to start 3.0 [95% Confidence Interval (CI), 1.1–4.9] days earlier on average than in the 1990s (1994–2000). The average peak value and annual total of daily counted airborne pollen have increased by 42.4% (95% CI, 21.9–62.9%) and 46.0% (95% CI, 21.5–70.5%), respectively. Changes of pollen season timing and airborne levels depend on latitude, and are associated with changes of growing degree days, frost free days, and precipitation. These changes are likely due to recent climate change and particularly the enhanced warming and precipitation at higher latitudes in the contiguous United States.